Dilema Etis Pekerja Sosial dalam Menerapkan Self-Determination dalam Penanganan Korban Kekerasan di Rifka Annisa Yogyakarta - Pebri Yanasari (Counselle| Journal of Islamic Guidance and Counseling, 2021)
Social worker as a profession based on help and assistance. One of them has the main task of trying to solve problems for individuals and groups. In handling it, social workers are the same as other professions, namely having a certain code of ethics in providing services to their clients. With regard to violence against women, the values and ethics of social workers can be applied in dealing with this problem. The method used in this research is descriptive qualitative, the data obtained from the results of interviews with institutions. For the approach, researchers used a phenomenology approach. The sources come from media references and other supporting books. In this case, the social worker at Rifka Annisa Yogyakarta tries to be wise and neutral towards the client in establishing a good relationship with the client's problems. The series of mentoring received by the client ends when the client / victim has carried out Self-Determination (self-determination) where the final decision is determined by the client / victim so that in handling the social worker experiences a dilemma when the decision is not in line with the process that has been done with the client.